2020
DOI: 10.1002/ddr.21722
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside protects against rhabdomyolysis‐induced acute kidney injury through PPAR‐γ agonism in rats

Abstract: We explored the potential role of peroxisome proliferator activated receptor‐γ (PPAR‐γ) in stevioside‐mediated renoprotection using rhabdomyolysis‐induced acute kidney injury (AKI) model in rats. Rhabdomyolysis refers to intense skeletal muscle damage, which further causes AKI. Glycerol (50% w/v, 8 ml/kg) was injected intramuscularly in rats to induce rhabdomyolysis. After 24 hr, AKI was demonstrated by quantifying serum creatinine, urea, creatinine clearance, microproteinuria, and electrolytes in rats. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In summary, in most cases, supplementation with ST mixed with high doses of L-arginine or Cr(III) was found to be most effective in alleviating hepatic, pancreatic, and renal abnormalities in diabetic animals. Such an impact on the liver, pancreas or kidneys was reported in many previous studies, which can be explained by the overall protecting property of Stevia rebaudiana leaves and/or its isolated compounds [ 28 , 60 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 96 , 97 , 98 , 99 , 100 ], L-arg [ 78 , 79 , 91 , 92 , 101 , 102 ] and Cr(III) [ 58 , 80 , 81 , 82 , 94 , 95 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In summary, in most cases, supplementation with ST mixed with high doses of L-arginine or Cr(III) was found to be most effective in alleviating hepatic, pancreatic, and renal abnormalities in diabetic animals. Such an impact on the liver, pancreas or kidneys was reported in many previous studies, which can be explained by the overall protecting property of Stevia rebaudiana leaves and/or its isolated compounds [ 28 , 60 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 96 , 97 , 98 , 99 , 100 ], L-arg [ 78 , 79 , 91 , 92 , 101 , 102 ] and Cr(III) [ 58 , 80 , 81 , 82 , 94 , 95 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 58%
“…The diet with ST and high doses of both L-arg and Cr(III) was the most effective in improving renal function, as the rats receiving this combination displayed no degeneration of Bowman’s capsule, no tubular degeneration, and no interstitial lymphocytic infiltrate. In addition, other authors confirm ST to have beneficial effects on kidney malfunctions [ 87 ] due to its regulatory action in PPAR-γ gene expression [ 88 , 89 ] or the ability to inhibit DNA fragmentation in the organ [ 90 ]. L-arg influences kidneys; however, this influence tends to be dose-dependent [ 91 ] and could both ameliorate a number of kidney diseases (e.g., hypertension, ureteral obstruction, kidney hypertrophy, glomerular thrombosis, or diabetic nephropathy) [ 92 ] and negatively affect creatinine clearance rate and/or glomerular filtration rate, and thus increase the risk of developing chronic kidney disease [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood urea nitrogen (BUN), serum creatinine (Scr), serum albumin (ALB), total cholesterol (TC), serum triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and urine albumin were measured using an automatic analyzer. Creatinine clearance was estimated using this formula: 29 Creatinine clearance ¼ Urine creatinine  Urine volume Serum creatinine  24  60  animal body weight :…”
Section: Biochemical Analysis Of Urine and Blood Samplesmentioning
confidence: 99%
“…Thiazolidinediones, such as pioglitazone, are insulin sensitizing agents that target Peroxisome Proliferators Activated Receptors (PPARs) to regulate gene expression and thereby decrease hepatic gluconeogenesis, increase adiponectin concentrations, and increase insulin-dependent glucose uptake in muscle and fat tissues ( 131 ). Studies have previously demonstrated a possible role for PPARs in the protection against AKI ( 132 134 ) and a large meta-analysis reported an association between treatment with thiazolidinediones and a significant decrease in urinary albumin excretion ( 129 ). Yet, no randomized controlled trials have been completed to thoroughly explore the acute and chronic kidney protective effects of thiazolidinediones ( 135 ).…”
Section: Therapeutic Strategies and Implicationsmentioning
confidence: 99%